The Rangeland Avenger - Brand, Max, 1892-1944 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Rangeland Avenger" by Max Brand is a Western novel that showcases themes of betrayal, revenge, and survival in a harsh desert landscape, likely written in the early 20th century. The story centers around Hal Sinclair, a carefree and innocent character who finds himself in dire straits after a tragic accident leaves him stranded in the desert with three resentful companions who ultimately abandon him. The unfolding narrative explores the darker side of human nature and the consequences of their selfish actions. At the start of the novel, the group of four men is on a mining expedition and grappling with the unforgiving desert environment. Hal Sinclair's youthful spirit contrasts sharply with the desperation and animosity that develops among his companions as they face the intensifying challenges of thirst and exhaustion. The situation escalates when Hal's horse injures itself, leaving him incapacitated and vulnerable. As Sinclairs' partners, filled with resentment and self-preservation instincts, decide to leave him behind in the unforgiving desert, they have unknowingly ignited a chain of events that will lead to a haunting conclusion. The opening sets the stage for themes of guilt and vengeance as the characters navigate their fateful choices against the backdrop of a harsh and merciless landscape. (This is an automatically generated summary.)
Release date is 2004-01-01
Produced by Suzanne Shell, Nick Thorp, Shon McCarley and PG Distributed Proofreaders
Keywords: Western stories